2011
DOI: 10.1042/bst20110654
|View full text |Cite
|
Sign up to set email alerts
|

Class 3 semaphorins and their receptors in physiological and pathological angiogenesis

Abstract: Class 3 semaphorins (Sema3) are a family of secreted proteins that were originally identified as axon guidance factors mediating their signal transduction by forming complexes with neuropilins and plexins. However, the wide expression pattern of Sema3 suggested additional functions other than those associated with the nervous system, and indeed many studies have now indicated that Sema3 proteins and their receptors play a role in angiogenesis. The present review specifically focuses on recent evidence for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…Previous studies have suggested that tumour development is inhibited by class 3 semaphorins (Staton, 2011). Indeed SEMA3B and SEMA3F have been described as tumour suppressors (Potiron et al, 2009) and our previous studies across the spectrum of breast disease have shown decreased expression of SEMA3A, 3B and 3F during the transition from in situ to invasive cancer (P b 0.014) (Staton et al, 2011b).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies have suggested that tumour development is inhibited by class 3 semaphorins (Staton, 2011). Indeed SEMA3B and SEMA3F have been described as tumour suppressors (Potiron et al, 2009) and our previous studies across the spectrum of breast disease have shown decreased expression of SEMA3A, 3B and 3F during the transition from in situ to invasive cancer (P b 0.014) (Staton et al, 2011b).…”
Section: Discussionmentioning
confidence: 92%
“…Originally identified as neuronal guidance proteins, more recent evidence has shown that individual class 3 semaphorins, most notably SEMA3A, SEMA3B and SEMA3F, may have anti-tumourigenic and antiangiogenic properties in human disease (reviewed by Staton (Staton, 2011)). It is therefore not surprising that these specific class 3 semaphorins are down-regulated in lung, ovarian, breast and oral cancers and, at least in some cases, there is evidence of an inverse correlation with markers of angiogenesis.…”
Section: Introductionmentioning
confidence: 98%
“…NRP1 acts as a co-receptor for VEGF and promotes VEGFR activation (44), VEGF bind to VEGFR to activate downstream signaling including PI3K, ERK and MAPK pathway, consequently promoting tumor cells proliferation, survival, differentiation, migration and angiogenesis (30). It was shown that Sema3 competes with VEGF for NRP1 binding and prevents angiogenesis (45,46). CRMP4 overexpression and NRP1 downregulation may suppress VEGF in autocrine and paracrine manner by both tumor cells and bone marrow cells, binding to tumor cells VEGFR blocks the downstream pathway.…”
Section: Discussionmentioning
confidence: 97%
“…These data demonstrate that endogenous zeb1a and foxo1a transcript levels change in response to decreased miR-145 activity. Finally, to address the consequence of miR-145-dependent downregulation of zeb1a or foxo1a during iSMC differentiation, we specifically blocked the miR-145-mediated downregulation of zeb1a and foxo1a in live embryos using target protector technology (Staton, 2011). Injections of zeb1a or foxo1a target protectors (zeb1a-TP or foxo1a-TP) in zebrafish embryos specifically impaired iSMC differentiation.…”
Section: Foxo1a Is Required For Lpm and Ismc Differentiationmentioning
confidence: 99%